HER2 signaling pathway activation and response of breast cancer cells to HER2-targeting agents is dependent strongly on the 3D microenvironment - Weigelt, Britta (2009)
Development of effective and durable breast cancer treatment strategies requires a mechanistic understanding of the influence of the microenvironment on response. Previous work has shown that cellular signaling pathways and cell morphology are dramatically influenced by three-dimensional (3D) cultures as opposed to traditional two-dimensional (2D) monolayers. Here, we compared 2D and 3D culture models to determine the impact of 3D architecture and extracellular matrix (ECM) on HER2 signaling and on the response of HER2-amplified breast cancer cell lines to the HER2-targeting agents Trastuzumab, Pertuzumab and Lapatinib. We show that the response of the HER2-amplified AU565, SKBR3 and HCC1569 cells to these anti-HER2 agents was highly dependent on whether the cells were cultured in 2D monolayer or 3D laminin-rich ECM gels. Inhibition of β1 integrin, a major cell–ECM receptor subunit, significantly increased the sensitivity of the HER2-amplified breast cancer cell lines to the humanized monoclonal antibodies Trastuzumab and Pertuzumab when grown in a 3D environment. Finally, in the absence of inhibitors, 3D cultures had substantial impact on HER2 downstream signaling and induced a switch between PI3K-AKT- and RAS-MAPK-pathway activation in all cell lines studied, including cells lacking HER2 amplification and overexpression. Our data provide direct evidence that breast cancer cells are able to rapidly adapt to different environments and signaling cues by activating alternative pathways that regulate proliferation and cell survival, events that may play a significant role in the acquisition of resistance to targeted therapies.